Single‐crystalline gold microplates grown on substrates by solution‐phase synthesis. Issue 8 (17th July 2015) - Wu, Xiaofei; Kullock, René; Krauss, Enno; Hecht, Bert
<x xml:space="preserve">Abstract</x> Single‐crystalline gold microplates grown directly on substrates by solution‐phase synthesis are reported. Substrate‐grown microplates exhibit high quality by avoiding small‐particle contamination and aggregation. Based on step‐growth and observation cycles of gold microplates on substrates, development of thickness, area and shape for a large number of individual microplates is investigated, and the growth mechanism is discussed. The microplate surface is found to remain smooth after regrowth in solution.